A Brief meditation on Daoist prayer - Bokenkamp, Stephen R. (Edinost in dialog, 2024)
Prayer is a little-studied aspect of religious experience. This is especially true for a religion such as Daoism (Taoism), a Chinese religion widely known for its meditation practices and often confused with Buddhism. But, beyond meditation, Daoism had, from its beginnings as an organized religion in the second century C. E., prescribed methods of verbal communication with the higher powers, both in communal and private settings. This essay explores a few of these in hopes of prompting further investigation.
Keywords: Buddhism; budizem; commitment; Daoism; daoizem; prestopki; refuge; transgressions; vows; zaobljube; zatočišče; zaveza(nost)